Pengaruh Personal Branding Sandiaga Uno Terhadap Minat Pemilih Perempuan Pada Pilpres 2019 - Gusmia Arianti; Rahman Asri (CoverAge: Journal of Strategic Communication, 2019)
Sandiaga Uno has been known as a young entrepreneur, and has the competence to maximize small and medium enterprises (MSMEs), and increase the participation of Jakarta citizens to build the Capital, by creating jobs. After being elected as the Deputy Governor of DKI Jakarta, Sandiaga Uno increasingly intensively in building his personal branding . The purpose of this study was to determine how much interest women voters have towards the personal branding strategy undertaken by Sandiaga Uno. To be able to lead Indonesia in 2019, Sandiaga Uno needs a strategy developed by Political public relations practitioners. The concept used in this study revolves around personal branding with three main elements in building good personal branding and aspects of interest that are complemented by the concepts of political marketing and political public relations. The approach used in this research is quantitative with a positivist paradigm. While the method used is a survey method in the form of a questionnaire distributed to 100 respondents who are women voters in the Greater Jakarta electoral district. The results of the study show that the influence of Sandiaga Uno's personal branding as a Vice-Presidential candidate on the interests of female voters by 53% can be categorized as strong.